SAOLHist – alla upplagor av SAOL i en och samma databas - Holmer, Louise (Nordiske Studier i Leksikografi, 2012)
The Swedish Academy Glossary (SAOL), has so far been published in 13 editions since 1874. The goal of the SAOLHist project is to put all editions of SAOL, some of which exist only on paper, into a single database. The number of lemmas of the Glossary has varied substantially over the years. The first edition comprised about 35,000 lemmas, while the latest has 125,000. In every new edition, new words have been added and obsolete ones have been excluded. With SAOLHist, it will be possible to search for a word’s timeline. Since all editions are searched simultaneously, information about the year of the first appearance of a word in the Glossary, or when it was subsequently removed, will be readily available.